Effectiveness of five artemisinin combination regimens with or without primaquine in uncomplicated falciparum malaria: an open-label randomised trial - Smithuis, Frank (Elsevier Science, The Lancet Pub. Group, 2010)
BACKGROUND: Artemisinin-combination therapy (ACT) is recommended as first-line treatment of falciparum malaria throughout the world, and fixed-dose combinations are preferred by WHO; whether a single gametocytocidal dose of primaquine should be added is unknown. We aimed to compare effectiveness of four fixed-dose ACTs and a loose tablet combination of artesunate and mefloquine, and assess the addition of a single gametocytocidal dose of primaquine. METHODS: In an open-label randomised trial in clinics in Rakhine state, Kachin state, and Shan state in Myanmar (Burma) between Dec 30, 2008, and March 20, 2009, we compared the effectiveness of all four WHO-recommended fixed-dose ACTs (artesunate–mefloquine, artesunate–amodiaquine, dihydroartemisinin–piperaquine, artemether–lumefantrine) and loose artesunate–mefloquine in Burmese adults and children. Eligible patients were those who presented to the clinics with acute uncomplicated Plasmodium falciparum malaria or mixed infection, who were older than 6 months, and who weighed more than 5 kg. Treatments were randomised in equal numbers within blocks of 50 and allocation was in sealed envelopes. All patients were also randomly assigned to receive either a single dose of primaquine 0·75 mg base/kg or not. Patients were followed up for 63 days. Treatment groups were compared by analysis of variance and multiple logistic regression. The primary outcome was the 63 day recrudescence rate. This study is registered with clinicaltrials.gov, number NCT00902811. FINDINGS: 155 patients received artesunate–amodiaquine, 162 artemether–lumefantrine, 169 artesunate–mefloquine, 161 loose artesunate–mefloquine, and 161 dihydroartemisinin–piperaquine. By day 63 of follow-up, 14 patients (9·4%; 95% CI 5·7–15·3%) on artesunate–amodiaquine had recrudescent P falciparum infections, a rate significantly higher than for artemether–lumefantrine (two patients; 1·4%; 0·3–5·3; p=0·0013), fixed-dose artesunate–mefloquine (0 patients; 0–2·3; p<0·0001), loose artesunate–mefloquine (two patients; 1·3%; 0·3–5·3; p=0·0018), and dihydroartemisinin–piperaquine (two patients 1·3%; 0·3–5·2%; p=0·0012). Hazard ratios for re-infection (95% CI) after artesunate–amodiaquine were 3·2 (1·3–8·0) compared with the two artesunate–mefloquine groups (p=0·01), 2·6 (1·0–6–0) compared with artemether–lumefantrine (p=0·04), and 2·3 (0·9–6·0) compared with dihydroartemisinin–piperaquine (p=0·08). Mixed falciparum and vivax infections were common: 129 (16%) had a mixed infection at presentation and 330 (41%) patients had one or more episodes of Plasmodium vivax infection during follow-up. The addition of a single dose of primaquine (0·75 mg/kg) reduced P falciparum gametocyte carriage substantially: rate ratio 11·9 (95% CI 7·4–20·5). All regimens were well tolerated. Adverse events were reported by 599 patients, most commonly vomiting and dizziness. Other side-effects were less common and were not related to a specific treatment. INTERPRETATION: Artesunate–amodiaquine should not be used in Myanmar, because the other ACTs are substantially more effective. Artesunate–mefloquine provided the greatest post-treatment suppression of malaria. Adding a single dose of primaquine would substantially reduce transmission potential. Vivax malaria, not recurrent falciparum malaria, is the main complication after treatment of P falciparum infections in this region. FUNDING: Médecins sans Frontières (Holland) and the Wellcome Trust Mahidol University Oxford Tropical Medicine Research Programme.